Techno-Economic of Rooftop Solar Power Plants for Residential Customer in Indonesia - Putri, Dianing Novita Nurmala; Fariz Maulana Rizanulhaq; Tyas Kartika Sari; Maula Sukma Widjaja; Chairul Gagarin Irianto (LPPM Universitas Negeri Semarang, 2024)
This study evaluates the financial viability of grid-connected rooftop photovoltaic (PV) systems across seven Indonesian residential types (2.75-19.8 kWp) under current market conditions. Using a discounted cash flow model with 8% discount rate and a 20-year project lifetime, key metrics including Net Present Value (NPV), Levelized Cost of Electricity (LCOE), and payback period have been analysed. Results demonstrate that system economics improve significantly with scale: while small systems (2.75 kWp) yield negative NPV (-Rp 9.71 million) and 12.4-year payback, larger installations (>7.7 kWp) achieve positive NPV (up to Rp 89.95 million for 19.8 kWp systems) and sub-10-year payback periods. The LCOE ranges from Rp 1,082-1,205/kWh, representing 11-36% cost savings compared to PLN's tiered tariffs (Rp 1,352-1,699.53/kWh). Monthly savings scale proportionally with system size, from Rp 323,378 (2.75 kWp) to Rp 2.84 million (19.8 kWp). A critical 7.7 kWp capacity threshold emerges for self-sustaining viability without subsidies, with 3500+ VA customers benefiting most due to higher avoided tariffs. These findings provide policymakers with evidence to design tiered incentive programs targeting underperforming market segments (<6 kWp systems), while confirming the commercial readiness of larger residential-commercial hybrid systems in Indonesia's solar transition.